The Effects of Intermittent Hypoxic–Hyperoxic Exposures on Lipid Profile and Inflammation in Patients With Metabolic Syndrome - Afina, A. Bestavashvili; Oleg, S. Glazachev; Alexander, A. Bestavashvili; Ines, Dhif; Alexander Yu, Suvorov; Nikita, V. Vorontsov; Denis, S. Tuter; Daria, G. Gognieva; Zhang, Yong; Chavdar, S. Pavlov; Dmitriy, V. Glushenkov; Elena, A. Sirkina; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Patients with metabolic syndrome (MS) tend to suffer from comorbidities, and are often simultaneously affected by obesity, dysglycemia, hypertension, and dyslipidemia. This syndrome can be reversed if it is timely diagnosed and treated with a combination of risk factors-reducing lifestyle changes and a tailored pharmacological plan. Interval hypoxic-hyperoxic training (IHHT) has been shown as an effective program in reducing cardiovascular risk factors in patients with MS even in the absence of exercise. However, the influence of IHHT on the lipid profile and inflammation in this clinical population remains relatively unknown. Methods: A prospective, single-center, randomized controlled trial was conducted on 65 (33 men) patients with MS aged 29–74 years, who were randomly allocated to the IHHT or control (sham) experimental groups. The IHHT group completed a 3-week, 5 days/week intermittent exposure to hypoxia and hyperoxia. The control (sham) group followed the same protocol but was breathing room air instead. The primary endpoints were the lipid profile (concentrations of total cholesterol [TC], low-density lipoprotein [LDL], high-density lipoprotein [HDL], and triglycerides [TG]) and the inflammatory factors such as high-sensitivity C-reactive protein (hs-CRP), galectin-3, heat shock proteins (Hsp70). The secondary endpoints were alanine aminotransferase (ALT), aspartate aminotransferase (AST), N-terminal pro-hormone of brain natriuretic peptide level (NTproBNP), transforming growth factor beta-1 (TGF-beta1), heart-type fatty acid-binding protein (H-FABP), and nitric oxide synthase 2 (NOS2). Results: There were no differences between the two groups but the different baseline values have affected these results. The IHHT group demonstrated pre-post decrease in total cholesterol (p = 0.001), LDL (p = 0.001), and TG levels (p = 0.001). We have also found a decrease in the CRP-hs (p = 0.015) and Hsp70 (p = 0.006) in IHHT-group after intervention, and a significant decrease in pre-post (delta) differences of NTproBNP (p < 0.0001) in the IHHT group compared to the control group. In addition, the patients of the IHHT group showed a statistically significant decrease in pre-post differences of ALT and AST levels in comparison with the control group (p = 0.001). No significant IHHT complications or serious adverse events were observed. Conclusions: The IHHT appears to improve lipid profile and anti-inflammatory status. It is a safe, well-tolerated procedure, and could be recommended as an auxiliary treatment in patients suffering from MS, however, the experiment results were limited by the baseline group differences. Clinical Trial Registration:ClinicalTrials.gov, identifier [NCT04791397]. Evaluation of the effect of IHHT on vascular stiffness and elasticity of the liver tissue in patients with MS.